Male germline stem cells developmental and regenerative potential - Orwig, Kyle E.; Brian P.; SpringerLink (Online Service). (Totowa, NJ Humana Press Imprint: Humana Press, 2011)
Scientists investigating germ cells have, over the past 15 years, originated discoveries and innovations that give us valuable insights into the mechanisms that regulate not just stem cell function, but human development in its widest sense. With contributions from some of the leading researchers in the field, Male Germline Stem Cells: Developmental and Regenerative Potential assesses the implications of these discoveries for understanding the fundamental biology of germline stem cells as well as their potential for human stem cell-based therapies. This monograph covers many of the fundamental issues now being explored by today?s generation of stem cell researchers, including the field's potential for regenerative medicine. Ranging from an assessment of the pluripotency of primordial germ cells and their possible applications in treating testicular cancer, to the recovery of once-mordant fertilization-competent sperm, this volume has it all. It is a reference point for any scientist involved in related research as well as being a timely summation of what could prove to be a hugely exciting and very fruitful area of inquiry.
Foreword -- Part I -- Germline developmental potential -- 1. Primordial germ cells to EG cells, Peter Donovan -- 2. Pluripotent stem cells from SSCs, Marco Seandel, Ilaria Falciatori, and Shahin Rafii -- 3. ES cells to gametes, Sonya M. Schuh-Huerta and Renee A. Reijo Pera -- Part II ? Spermatogonial stem cells -- 4. Morphometric description of the SSC pool in mammals, Dirk G. de Rooij -- 5. Spermatogonial stem cell transplantation and culture, Jonathan A. Schmidt and Ralph L. Brinster -- 6. Spermatogonial stem cell culture and in vitro assay, Makoto C. Nagano and Jonathan R. Yeh -- 7. Molecular signaling in SSCs, Olga M. Ocón-Grove and Jon M. Oatley -- 8. Spermatogonial stem cell niche, Shosei Yoshida -- Part III ? Translation and regenerative potential of spermatogonial stem cells in higher primates -- 9. Gonadotoxic therapies: effects on spermatogenesis and fertility, Gunapala Shetty, Gensheng Wang, and Marvin L. Meistrich -- 10. Testicular xenografting, Stefan Schlatt, Jose R Rodriguez-Sosa and Ina Dobrinski -- 11. SSC transplantation in primates, Brian P. Hermann and Kyle E. Orwig.
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Stem cells; Germ cells; Electronic books